Nuclear Actin in Development and Transcriptional Reprogramming - Misu, Shinji; Takebayashi, Marina; Miyamoto, Kei (Frontiers in Genetics, 2017)
Actin is a highly abundant protein in eukaryotic cells and dynamically changes its polymerized states with the help of actin-binding proteins. Its critical function as a constituent of cytoskeleton has been well-documented. Growing evidence demonstrates that actin is also present in nuclei, referred to as nuclear actin, and is involved in a number of nuclear processes, including transcriptional regulation and chromatin remodeling. The contribution of nuclear actin to transcriptional regulation can be explained by its direct interaction with transcription machineries and chromatin remodeling factors and by controlling the activities of transcription factors. In both cases, polymerized states of nuclear actin affect the transcriptional outcome. Nuclear actin also plays an important role in activating strongly-silenced genes in somatic cells for transcriptional reprogramming. When these nuclear functions of actin are considered, it is plausible to speculate that nuclear actin is also implicated in embryonic development, in which numerous genes need to be activated in a well-coordinated manner. In this review, we especially focus on nuclear actin’s roles in transcriptional activation, reprogramming and development, including stem cell differentiation and we discuss how nuclear actin can be an important player in development and cell differentiation.